2012
DOI: 10.1088/1741-2560/9/4/046005
|View full text |Cite
|
Sign up to set email alerts
|

Improved spatial targeting with directionally segmented deep brain stimulation leads for treating essential tremor

Abstract: Deep brain stimulation (DBS) in the ventral intermediate nucleus of thalamus (Vim) is known to exert a therapeutic effect on postural and kinetic tremor in patients with essential tremor. For DBS leads implanted near the caudal border of Vim, however, there is an increased likelihood that one will also induce paresthesia side-effects by stimulating neurons within the sensory pathway of the ventral caudal (Vc) nucleus of thalamus. The aim of this computational study was to 1) investigate the neuronal pathways m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 46 publications
5
92
0
1
Order By: Relevance
“…We believe that either the VPL nucleus is not included in our VIM DBS patients or there may be a habituation of the VPL to electrical stimulation. Nevertheless, computational models of DBS have shown a good correlation with an improvement of symptoms and reduction of adverse effects [13,14,27,45]. Considering the possible variations of the localization of the DRTT, also described in this atlas, we believe that the DRTT in the PSA/caudal Zi could be the common structure stimulated at different places in both our cohorts as well as in the other mentioned studies, as illustrated in Figure 1.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We believe that either the VPL nucleus is not included in our VIM DBS patients or there may be a habituation of the VPL to electrical stimulation. Nevertheless, computational models of DBS have shown a good correlation with an improvement of symptoms and reduction of adverse effects [13,14,27,45]. Considering the possible variations of the localization of the DRTT, also described in this atlas, we believe that the DRTT in the PSA/caudal Zi could be the common structure stimulated at different places in both our cohorts as well as in the other mentioned studies, as illustrated in Figure 1.…”
Section: Discussionsupporting
confidence: 54%
“…While numerous studies have suggested that the stimulation site correlated with the best clinical results in PD patients is located in the superior and lateral part of the STN [27,28,29,30], PSA DBS in PD patients have also suggested a positive effect on rigidity and bradykinesia. These findings should, however, be taken cautiously since the experience with PSA DBS is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The further development of new electrodes is also underway, with the goal of permitting more precise shaping and steering of the electrical field, through the use of multiple contacts along the electrode shaft [337,338], in order to better control unintended spread and optimal shaping of current flow. Obviously, the freedom of being able to use additional electrode contacts must be balanced against the resulting more complex programming requirements.…”
Section: Technical Developments and Future Of Neuromodulationmentioning
confidence: 99%
“…There have been several traditional methods described for the programming of DBS for ET [68]. These methods involve evaluating each of the four contacts for the threshold for both side effects and efficacy, adjusting the various parameters in a consistent pattern.…”
Section: Introductionmentioning
confidence: 99%